Use of feldspathic ceramics in a digital protocol: A clinical case - O. A. Naidyonova (Эндодонтия Today)
When starting to work within a digital protocol, especially with the ability to implement restorations directly at the patient’s chairside, doctors face the challenge of selecting the appropriate material. The correct choice of block can help achieve a highly aesthetic and quality result in a short time. Modern CAD/CAM systems allow for the fabrication of a single restoration at the patient’s chairside in just 10 minutes, as demonstrated in this clinical case.